Paleogeography arid zone of Kazakhstan - Akpambetova, K.M.; Bujdoso, Z.; Rahmetova, A.A. (Fundamental and Experimental Biology, 2016)
Modern Kazakhstan deserts for many geological epochs were areas of the Earth's crust immersion. As a result, there marine and continental powerful unconsolidated sediments have accumulated. The alternation of the sediments indicates a change in repeated transgressions and regressions of the sea caused by centuries of slow vertical oscillation of the land. The complexity of the geological structure of Kazakhstan conditioned by participation of the different rock complexes. The age of rocks varies widely. Paleogeographic history of the arid zone shows the relation of the present topography of the arid zone with ancient geological structure.